BNCT for primary synovial sarcoma. (March 2021) - Fujimoto, Takuya; Suzuki, Minoru; Kuratsu, Shigeyuki; Fujita, Ikuo; Morishita, Masayuki; Sudo, Tamotsu; Sakuma, Toshiko; Nakamatsu, Yuta; Sakurai, Yoshinori; Takata, Takushi; Tamari, Yuki; Tanaka, Hiroki; et al.
Abstract: Synovial sarcoma is a rare tumor requiring new treatment methods. A 46-year-old woman with primary monophasic synovial sarcoma in the left thigh involving the sciatic nerve, declining surgery because of potential dysfunction of the affected limbs, received two courses of BNCT. The tumor thus reduced was completely resected with no subsequent recurrence. The patient is now able to walk unassisted, and no local recurrence has been observed, demonstrating the applicability of BNCT as adjuvant therapy for synovial sarcoma. Further study and analysis with more experience accumulation are needed to confirm the real impact of BNCT efficacy for its application to synovial sarcoma. Highlights: The first evaluation of BNCT for treating primary synovial sarcoma. The first patient with synovial sarcoma receiving two courses of BNCT. The first instance of partial control of tumor by BNCT as adjuvant therapy.